Investigating Students’ Problems In Writing Recount Text To The Eight Grade Students - sulaiman sulaiman (Journal of English Language Learning, 2022)
Abstract. This study aimed to describes students’ writing recount problem. This research used descriptive method and was conducted at SMP Negeri 20 Pontianak. It revealed the most serious problem in writing recount text was in the area of grammar. It found when the students wrote recount text which applied past tense with regular or irregular verb. The second problem came from the vocabulary aspect. It happened when the students demonstrated to state the main idea and include choosing the word that supporting in writing recount text. The third problems found in the area of organization aspects. It happened when the students composed the text paragraph coherently. The last problems found in the part of mechanics. It came when the students wrote down the recount text paragraph in the zone of spelling and punctuation